COMPARISON OF LEARNING OUTCOMES OF 11TH GRADE STUDENTS AFTER BEING TAUGHT USING THE TEAMS GAMES TOURNAMENT (TGT) AND MAKE A MATCH (MAM) LEARNING MODELS ON THE TOPIC OF LIMIT AlGEBRAIC FUNCTIONS - Masruroh, Masruroh; Sari, Dwi Ivayana (Prima: Jurnal Pendidikan Matematika, 2024)
Lately, there has been a decline in students' learning outcomes due to the use of teaching models that are not suitable for the teacher. There are many teaching models that can be used to create the desired interaction. One of them is by implementing cooperative learning models. Some appropriate cooperative learning models to engage students' attention are Teams Game Tournament (TGT) and Make A Match (MAM). The aim of this research is to determine the comparison of learning outcomes of 11th grade students who were taught using the TGT and MAM learning models on the topic of limit of algebraic functions, and to determine which learning model, TGT or MAM, is more effective for 11th grade students. This research is a quantitative study. There are two classes involved in this research, namely Experiment Class 1 (TGT) and Experiment Class 2 (MAM). The subjects of this research are 11th grade students of MA Raudlatul Ulum, Klampis. The data analysis technique used in this research is inferential statistics and n gain score test. The results of this research show that there is a significant difference in learning outcomes between the application of the TGT and MAM learning models on the limit of algebraic functions. The research findings indicate that the MAM learning model is more effective for 11th grade students with an average score of 78% compared to the TGT learning model with an average score of 75%.Keywords: Learning Outcomes, TGT, MAM